Bactericidal activity of acetone extract of Alpinia galanga on multidrug resistant clinical isolates of Enterococcus faecalis - Dr. Ramamoorthi Arularasi Aberna; Dr. Kesani Prabhakar (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: The objective of the study was to evaluate the inhibitory activity of five traditional Indian medicinal herbs against multidrug resistant clinical isolates of E. faecalis.Methods: Sixty five E. faecalisderived from clinical specimens were tested for their resistance pattern to 7 antibiotics by disc diffusion method. Extracts from 5 medicinal plant parts were obtained and tested for inhibitory activity against multi drug resistant clinical E. faecalisisolates. The minimum bactericidal concentration (MBC) for the active plant extract exhibiting highest activity towards the susceptible isolateswas determined by macro broth dilution method followed by sub culturing on agar plate.Results: All the clinically derived E. faecalis isolates were resistant to two or more antibiotics. Acetone extract of Alpiniagalanga inhibited 67.69% of E. faecalis and concentration of <5.0mg/ml was found to exert bactericidal activity against multi drug resistant isolates.Conclusion: Acetone extract of A. galanga exhibit bactericidal activity against multi-drug resistant clinical isolates of E. faecalis and hence could be potential phytotherapeutic candidate.